An indicator for national systems of innovation: Methodology and application to industrialized countries - Heike Belitz; Marius Clemens; Christian von Hirschhausen; Jens Schmidt-Ehmcke; Axel Werwatz; Petra Zloczysti (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
We develop a composite indicator measuring the performance of national innovation systems. The indicator takes into account both hard factors that are quantifiable (such as R&D spending, number of patents) and soft factors like the assessment of preconditions for innovation by managers. We apply the methodology to a set of 17 industrialized countries on a yearly basis between 2007 and 2009. The indicator combines results from public opinion surveys on the process of change, social capital, trust and science and technology to achieve an assessment of a country's social climate for innovation. After calculating and ranking the innovation indictor scores for the 17 countries, we group them into three classes: innovation leader, middle group and end section. Using multiple sensitivity analysis approaches, we show that the indicator reacts robustly to different weights within these country groups. While leading countries like Switzerland, the USA and the Nordic countries have an innovation system with high scores and ranks in every sub indicator, the middle group consisting among others of Germany Japan, the UK and France, can be characterized by higher variation within ranks. In the end section, countries like Italy and Spain have bad scores for almost all indicators.
Keywords: O30; C81; H52; 330; national systems of innovation; composite indicators; ranking; Innovation; Innovationspolitik; Wirtschaftsindikator; Ranking-Verfahren; Industriestaaten